2017
DOI: 10.3390/met7050157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effect of Melt Treatments on Melt Quality in Al-7wt %Si-Mg Alloys

Abstract: Abstract:The effects of degassing, holding time and melt additions (Sr, Sr + Ti, Ti, B and B + Sr) on the quality of A356 melts were examined. A total of 120 reduced pressure test samples were collected. Pores in these samples were analyzed via digital image processing to determine the number density of pores as well as the statistical distribution of their sizes. Results showed that in all cases, degassing with argon reduced the number of defects regardless of the additions made to the melts. Moreover, all ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…The main observation can be seen on the RPT samples cross-sections ( figure 1) where the size of pores is getting smaller and the number of pores is decreasing. Uludag [18] had reported a similar finding where the Sr modified melt had shown an increased number of smaller pores. Liu [8] also reported the same findings.…”
Section: Introductionmentioning
confidence: 64%
“…The main observation can be seen on the RPT samples cross-sections ( figure 1) where the size of pores is getting smaller and the number of pores is decreasing. Uludag [18] had reported a similar finding where the Sr modified melt had shown an increased number of smaller pores. Liu [8] also reported the same findings.…”
Section: Introductionmentioning
confidence: 64%
“…Due to these bifilms that are extrinsic, nucleation is completely bypassed, and pores form simply by the opening of bifilms [6]. There is growing evidence in the literature on the role of bifilms on causing pores [6,13,[16][17][18][19][20][21][22][23][24][25][26] and leading to hot tears [27,28]. Oxides are inevitable on the surface of liquid aluminum and serve as a protective film over the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby the porosity was decreased since bifilms were unable to unravel. Uludag et al [26][27][28][29] studied the influence of Sr on bifilm index. It was found that addition of Sr had decreased the size and length of pores which was attributed to the healing of bifilms as was reported by Ramin [25,30,31].…”
Section: Introductionmentioning
confidence: 99%